Gait Changes with Balance-Based Torso-Weighting in People with Multiple Sclerosis - Gorgas, Anna-Maria (Physiother Res Int, 2014)
BACKGROUND AND PURPOSE: People with multiple sclerosis (PwMS) commonly have mobility impairments that may lead to falls and limitations in activities. Physiotherapy interventions that might improve mobility typically take several weeks. Balance-based torso-weighting (BBTW), a system of strategically placing light weights to improve response to balance perturbations, has resulted in immediate small improvements in clinical measures in PwMS, but changes in spatio-temporal gait parameters are unknown. The purpose was to investigate the effects of BBTW on gait parameters in PwMS and healthy controls. METHODS: Design: non-randomized controlled experiment PARTICIPANTS: 20 PwMS and 20 matched healthy controls PROCEDURES: PwMS walked on an instrumented mat at their fastest speed for three trials each in two conditions: without BBTW then with BBTW. Healthy controls walked in both conditions at two speeds: their fastest speed, and at velocities equivalent to their matched PwMS. RESULTS: Averaged gait trials showed that, with BBTW, PwMS had significantly increased velocity (p=.002), cadence (p=.007), and time spent in single-limb support (p=.014), with decreased time in double-limb support (p=.004). Healthy controls increased velocity (p=.012) and cadence (p=.015) and decreased support base (p=.014) in fast trials with BBTW; at matched velocities, step length (p=.028) and support base (p=.006) were significantly different from PwMS. All gait variables in healthy controls at fast speeds were significantly different from PwMS walking at their fastest speeds. DISCUSSION: All participants showed increases in gait velocity and cadence during fast walk with BBTW. Improvements in time spent in single- and double-limb support by PwMS with BBTW may reflect greater stability in gait. Future research might ascertain if these immediate improvements could enhance effectiveness of longer-term physiotherapy on functional mobility in PwMS.